Phytochemical Investigation And Antibacterial Activities Of Leaves Of With ania Somnifera - Almaz Geremew (ASTU, 2015)
In this research, a phytochemical study has been undertaken on the leaves of Withania somnifera and the solvent extract of the plant has been conducted. Withania somnifera is indigenous to Eastern and Southern Africa and is occasionally cultivated for its medicinal uses, including antibacterial, anticancer, and for the treatment of ulcers, wounds, stomachache, toothache, asthma, throat and chest infection. The methanol extract of the leaves of Withania somnifera lead to the isolation of two compounds W.S -24 and W.S-36 The structure of compound W.S-24 and W.S-36 was determined by means of spectroscopic methods (IR, 1H-NMR, 13C NMR, and DEPT). The methanol extract which also checked for its antibacterial activity. It exhibited modest activity.
Keywords: : Withania somnifera, WS-24, WS-36, NMR.